Potential Effects of Dietary Cabanin® CSD on Growth Performance and Biochemical and Antioxidant Responses of Nile Tilapia (Oreochromis niloticus) - Vo Van Tuan; Vo Thi Thanh Binh; Le Thanh Hung (Fishes, 2024)
This study was conducted to investigate the potential effects of natural polyphenol antioxidant (Cabanin® CSD provided by R2 Agro, Denmark)-supplemented diets on the growth performance and biochemical and antioxidant responses of Nile tilapia (Oreochromis niloticus). The fish were fed two control diets (low and high levels of vitamin C and vitamin E without added Cabanin® CSD) and two experimental diets with Cabanin® CSD supplementation for 10 weeks. After the trial, the specific growth rate, feed utilization, and survival rate were observed. The blood biochemical parameters, consisting of superoxide dismutase activity, malondialdehyde, cortisol, and glucose, were measured. The presence of malondialdehyde in the flesh meat of the tilapia was also evaluated during refrigerated storage. The fish was then challenged with 60 mg/L ammonia for 168 h. The survival rate and biochemical parameters of the blood (glucose and cortisol) were recorded after exposure to ammonia. The results show that the growth performance of tilapia was significantly improved by Cabanin® CSD supplementation (p < 0.05), while the survival rates were similar between control and Cabanin® CSD-supplemented diet groups. Superoxide dismutase activity and malondialdehyde levels in the blood serum were significantly different between the control and Cabanin® CSD-supplemented diet groups (p < 0.05). The malondialdehyde levels were significantly higher in the control group in comparison with the Cabanin® CSD-supplemented groups at day 1 and day 7 of refrigerated storage (p < 0.05). In the ammonia challenge test, the highest survival rate was observed in the Cabanin® CSD-supplemented diet groups compared to the control group. The fish serum glucose and cortisol levels increased in all the Cabanin® CSD-supplemented diet groups. In general, diets featuring Cabanin® CSD supplementation were found to exert beneficial effects on the growth performance, antioxidant capacity, and biochemical activity of tilapia under ammonia stress.